War Crimes In Palestine From The Perspective Of The International Criminal Court (ICC) - Sitompul, Ariman (International Asia Of Law and Money Laundering (IAML), 2023)
The purpose of this study is to find out what becomes the main considerations of an entity recognized as a state by law war crimes from an International Criminal perspective Court (ICC) . Types of research used in this study is juridical normative, with the approach of legislation, case study, and historical approach. The results of this study Article 1 of the montevidio Convention states that there are four criteria that must be met by a new state to become a sovereign state, namely; the existence of a permanent population, Territory, government, and the capacity of the state as a support in relations with other countries. There is also a recognition of a state that is divided into two forms, namely de jure recognition and de facto, Palestine has been recognized de jure because in its practice as evidenced by conducting international agreements with several countries. The ICC has four types of jurisdiction: personal, criminal, temporal and territorial. Pleased that we can return to the automatic principle of locus delicti that Israel commits war crimes in the Palestinian territories and supported by the jurisdiction of the court, then the ICC is more than enough to judge Israel using the jurisdiction of the automatic principle contained the Rome statute of 1998. The unwilling and unable criteria can be extended by Article 13 of the 1998 Rome Statute, which states that the ICC has three powers to investigate international crimes, if there is a conviction that one or all of the parties committed international crimes in accordance with Article 5 of the 1998 Rome Statute.